Visions of God and the Rationality of the Surveillance State-A still in progress - Francesca, B. (university of jaffna, 2025)
This presentation captures the flow, the porousness, the multiplicity, as well as the hidden transformational potential of the binary between being, and non being during times of resistance to the Sri Lankan state from the north, and north east between the years of 1990 and 2010. This time period was chosen as it captured a climate of fear due to the increasing resistances from the above mentioned areas which resulted in bombings and killings, and led to changes in the spatial map of the city as the State transitioned into a Surveillance State based on the rationality of checkpoints, identity documents and body searches. This presentation illustrates that the Surveillance State, though embedded in incoherence, used the concept of rationality to break bodies into objects in which they touch the state of non-being. Thus, at the binary between being and non-being lie the dynamics of “truth production” which involves the Rational, Surveillance State and its dynamics. The resistance to this Surveillance State also arises in this same binary between being and non-being as some of those who have been physically broken begin to see visions of God, and the power of this vision awakens an important historical collective memory in the torturer which unsettles linear narratives of State power. Thus, this binary between being and non-being in the above context opens a crevice into the processes of State power and collective memory, thus illustrating that binaries are fluid, porous and rich with historical processes, struggles for power and future transformations. The non-being in this presentation lies at the margins of bare life in a state of embodiment, which is also present in the larger cultural imagination.